2018
DOI: 10.1038/s41598-018-19189-1
|View full text |Cite|
|
Sign up to set email alerts
|

High-temperature operation of electrical injection type-II (GaIn)As/Ga(AsSb)/(GaIn)As “W”-quantum well lasers emitting at 1.3 µm

Abstract: Electrical injection lasers emitting in the 1.3 μm wavelength regime based on (GaIn)As/Ga(AsSb)/(GaIn)As type-II double “W”-quantum well heterostructures grown on GaAs substrate are demonstrated. The structure is designed by applying a fully microscopic theory and fabricated using metal organic vapor phase epitaxy. Temperature-dependent electroluminescence measurements as well as broad-area edge-emitting laser studies are carried out in order to characterize the resulting devices. Laser emission based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Characteristic temperatures of T 0 = (76 ± 7) K and T 1 = (84 ± 9) K are determined using the same procedure as outlined above. Furthermore, a non-exponential behavior of T 1 is observed similar to previous studies [15]. A separate analysis of T 1 between 10°C & 60°C and 70°C & 100°C yields values of T 1 = (126 ± 7) K and T 1 = (33 ± 3) K, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Characteristic temperatures of T 0 = (76 ± 7) K and T 1 = (84 ± 9) K are determined using the same procedure as outlined above. Furthermore, a non-exponential behavior of T 1 is observed similar to previous studies [15]. A separate analysis of T 1 between 10°C & 60°C and 70°C & 100°C yields values of T 1 = (126 ± 7) K and T 1 = (33 ± 3) K, respectively.…”
Section: Resultssupporting
confidence: 87%
“…A differential efficiency of 58 % and a threshold current density of 0.31 kA/cm 2 are deduced from the measurement taken at 20°C. These results imply an improvement by 41 % while the threshold current density is reduced by −69 % compared to previous studies [15]. Furthermore, operation based on the fundamental type-II transition is verified by investigating the spectral properties of sample A above threshold in the temperature range between 10°C and 100°C.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…First experimental observation of room‐temperature lasing from a (Ga,In)As/Ga(As,Sb)/(Ga,In)As W‐type structure has been reported in 2002 [10]. Recently, promising results have been achieved for (Ga,In)As/Ga(As,Sb)/(Ga,In)As W‐type structures showing laser emission at 1.3 μm [11]. Since Bi incorporation in GaAs shows an upward shift of the valance band by ∼53 meV/%Bi, replacing Ga(As,Sb) with Ga(As,Bi) gives an exciting path for novel laser devices [12].…”
Section: Introductionmentioning
confidence: 99%
“…In pulsed operation, electrical injection pumped edge-emitting gain chips based on type-II QW design have produced pulses with 1.4 W output power per facet [2]. Not only has it been demonstrated that type-II QWs are able to reach new wavelength ranges but the studies of the systems in the 1.3 µm region also showed that the type-II QW configuration tends to be less sensitive to changes in temperature [3].…”
Section: Introductionmentioning
confidence: 99%